Advanced 3-dimensional signal processing for synthetic aperture radar - Zhou, Lie. (2011)
The use of synthetic aperture radar (SAR) is well established worldwide. Modern airborne and spaceborne imaging radars, known as SAR, are capable of producing high-quality pictures of the earth’s surface while avoiding some of the shortcomings of certain other forms of remote imaging system. This project describes the three dimensional synthetic aperture radar (SAR) imaging generation by interferometry method. First the principle theory for synthetic aperture radar is examined. Then concepts, techniques and applications of interferometric synthetic aperture radar (IFSAR, also abbreviated as InSAR) are introduced. In the second part, the study of IFSAR image formation using MATLAB is explained and results of imaging generation by interferometry method are done. Finally some improvements to obtain better image is suggested by comparing interferometry with another method called radargrametry.